Are We Ready to Treat Diffuse Large B-cell and High-Grade Lymphoma According to Major Genetic Subtypes?. Issue 5 (October 2019) - Chiappella, Annalisa; Crombie, Jennifer; Guidetti, Anna; Vitolo, Umberto; Armand, Philippe; Corradini, Paolo
Abstract : Abstract: Diffuse Large B-Cell Lymphoma (DLBCL) is a clinically and biologically heterogeneous disease. The revised Classification of Lymphoproliferative diseases published in 2016 (WHO, 2016) refined the previous DLBLC subtypes and identified four categories: DLBCL not otherwise specified (NOS), other lymphomas of large B cells, high grade B-cell lymphoma, and B-cell lymphoma unclassifiable. High grade B-cell lymphomas include the entities carrying MYC, BCL2 and/or BCL6 translocations or cases with blastoid morphology without DH translocations. This classification also acknowledges the cell of origin (COO) classification, that has only a limited impact on the choice of frontline treatment for DLBCL, as most patients still receive R-CHOP chemoimmunotherapy. Attempts to improve the outcomes of specific subgroups, especially COO groups, have so far had limited success. Newer analyses have further subdivided DLBCL into genomically distinct subsets, not yet incorporated in the WHO classification, which may facilitate targeted approaches to therapy. In this review, we discuss the subgroups that are recognized by the WHO 2016 classification, review the newer genomic data, and speculate on how this could alter the treatment landscape of DLBCL in the future. We also discuss novel approaches to salvage therapy in the broad context of the heterogeneity of DLBCL.